Tempat Peribadatan Hindu Masa Sriwijaya - Hudaidah, Hudaidah; Elsabela, Elsabela (Jayapangus Press, 2022)
Classical ruins in South Sumatra are often engrossed in the existence of the Srivijaya kingdom in the past. This is because the reign of Srivijaya lasted a long time from the VII century to the XIV century AD. One of the classical or Hindu influences is the Bumiayu temple in the village of Bumiayu in the Tanah Abang sub-district. The Bumiayu temple complex is a joint temple complex between Buddhists and Hindus. Based on these findings, it is interesting to study how temples for Hindu worship can coexist with Buddhist temples. The purpose is to describe the Hindu place of worship during the Srivijayan era at Bumiayu Temple. This research method uses a historical methodology. The conclusion that can be drawn is that the Bumiayu temple is a place of relics and worship of gods as well as a place of worship for the ancestors of Hindus during the Sriwijaya era.